Viabilidade das células mononucleares de sangue periférico humano em diferentes meios de estocagem de dentes avulsionados - DOI: 10.4025/actascihealthsci.v25i1.2301 - Denise Fernanda de Melo; Ana Maria Sell; Carlos Marcelo Lopes; Mirian Murabayashi Hidalgo (Acta Scientiarum. Health Sciences, 2008)
This study aims to compare the viability of the human mononuclear cells for 24 hours at 20ºC in different storage media for avulsed teeth: distillated water, type C pasteurized milk, whole ultra-pasteurized milk, saliva, physiologic solution, and McCoy culture cells medium. At times 0, 30min, 1h, 3h, 6h, 10h and 24h was extracted sample and analyzed for the exclusion with Trypan blue method. The pH of each storage medium was also measured. The tests indicated that all media performed better than water (p < 0,05). Since 3h, both types of milk and the McCoy showed viability statistically better (p < 0,05) than saliva and physiologic solution. There was no difference between two types of milk and it was not possible to make the reading of 24 hours due to deposit of the biologic material. The milk, saliva, and McCoy showed pH compatible with the cell proliferation. The results suggest that McCoy culture medium and milk are effective to storage of the avulsed teeth for making possible the maintenance of the cell viability.